Social Norms, Mental Models and other Behavioral Drivers of Petty Corruption– the Case of Uganda - Stahl, Cosimo; Camargo, Claudia Baez (Basel Institute on Governance, 2017)
This policy brief summarizes the main findings and lessons learned from research on corruption, social norms and behaviors in Uganda. The empirical evidence indicates that behavioral factors associated to social practices and collective understandings play a role in shaping Ugandan citizens’ attitudes towards petty corruption and in fuelling practices such as bribery and favoritism. On the basis of the research findings, policy recommendations are put forward aiming to contribute to the development of anti-corruption interventions that incorporate behavioral insights in their design and implementation.